Variants in the GPR146 Gene Are Associated With a Favorable Cardiometabolic Risk Profile. Issue 10 (1st September 2022) - Rimbert, Antoine; Yeung, Ming W.; Dalila, Nawar; Thio, Chris H.L.; Yu, Haojie; Loaiza, Natalia; Oldoni, Federico; van der Graaf, Adriaan; Wang, Siqi; Said, M. Abdullah; Blauw, Lisanne L.; Girardeau, Aurore; et al.
Abstract : Background: In mice, GPR146 (G-protein–coupled receptor 146) deficiency reduces plasma lipids and protects against atherosclerosis. Whether these findings translate to humans is unknown. Methods: Common and rare genetic variants in the GPR146 gene locus were used as research instruments in the UK Biobank. The Lifelines, The Copenhagen-City Heart Study, and a cohort of individuals with familial hypobetalipoproteinemia were used to find and study rare GPR146 variants. Results: In the UK Biobank, carriers of the common rs2362529-C allele present with lower low-density lipoprotein cholesterol, apo (apolipoprotein) B, high-density lipoprotein cholesterol, apoAI, CRP (C-reactive protein), and plasma liver enzymes compared with noncarriers. Carriers of the common rs1997243-G allele, associated with higher GPR146 expression, present with the exact opposite phenotype. The associations with plasma lipids of the above alleles are allele dose-dependent. Heterozygote carriers of a rare coding variant (p.Pro62Leu; n=2615), predicted to be damaging, show a stronger reductions in the above parameters compared with carriers of the common rs2362529-C allele. The p.Pro62Leu variant is furthermore shown to segregate with low low-density lipoprotein cholesterol in a family with familial hypobetalipoproteinemia. Compared with controls, carriers of the common rs2362529-C allele show a marginally reduced risk of coronary artery disease ( P =0.03) concomitant with a small effect size on low-density lipoprotein cholesterol (average decrease of 2.24 mg/dL in homozygotes) of this variant. Finally, mendelian randomization analyses suggest a causal relationship between GPR146 gene expression and plasma lipid and liver enzyme levels. Conclusions: This study shows that carriers of new genetic GPR146 variants have a beneficial cardiometabolic risk profile, but it remains to be shown whether genetic or pharmaceutical inhibition of GPR146 protects against atherosclerosis in humans.